Analyzing annual changes in network structures of a social media application-based information-sharing system in a Japanese community - Junji Haruta; Sho Tsugawa; Kazunari Ogura (BMC, 2022)
Abstract Background Understanding the evolution of social network services (SNSs) can provide insights into the functions of interprofessional information-sharing systems. Using social network analysis, we aimed to analyze annual changes in the network structure of SNS-based information sharing among healthcare professionals over a 3-year period in Japan. Methods We analyzed data on SNS-based information sharing networks with online message boards for healthcare professionals for 2018, 2019, and 2020 in a Japanese community. These networks were created for each patient so that healthcare professionals could post and view messages on the web platform. In the social network analysis (SNA), healthcare professionals registered with a patient group were represented as nodes, and message posting and viewing relationships were represented as links. We investigated the structural characteristics of the networks using several measures for SNA, including reciprocity, assortativity and betweenness centrality, which reflect interrelational links, the prevalence of similar nodes with neighbors, and the mediating roles of other nodes, respectively. Next, to compare year-to-year trends in networks of patients overall, and between receiving nursing care levels 1-3 (lighter care requirement) and levels 4-5 (heavier care requirement), we described the annual structural differences and analyzed each measure for SNA using the Steel-Dwass test. Results Among 844, 940, and 1063 groups in each year, groups for analysis in care levels 1-3/4-5 were identified as 106/135, 79/89, and 57/57, respectively. The overall annual assessment showed a trend toward increased diameter and decreased density, but the differences were not significant. For those requiring care levels 1-3, assortativity decreased significantly, while for those requiring care levels 4-5, reciprocity decreased and betweenness centrality increased significantly. No significant differences were found in the other items. Discussion This study revealed that the network of patients with a lighter care requirement had more connections consisting of nodes with different links, whereas the network of patients with a heavier care requirement had more fixed intermediary roles and weaker interrelationships among healthcare professionals. Clarifying interprofessional collaborative mechanisms underlying development patterns among healthcare professionals can contribute to future clinical quality improvement.